Implementation of School-Based Management at SD Inpres Kema II - Rau, Deissy Wenda; Sumual, Tinneke E. M; Krowin, Marthinus (International Journal Labs, 2023)
This research aims to examine: (1) the implementation of school-based management at SD Inpres Kema II, (2) the role of the principal in implementing school-based management at SD Inpres Kema II, (3) the role of the community as a stakeholders in the implementation of school-based management at SD Inpres Kema II. SD Inpres Kema II, (4) Obstacles encountered in implementing school-based management at SD Inpres Kema II, (5) How to overcome obstacles in implementing school-based management at SD INpres Kema II. This study used a qualitative approach with case study design. The data collection techniques used were: (1) Observation, (2) In-depth Interviews, and (3) Documentation Study. From the results of data analysis, the following findings were obtained: (1) SD Inpres Kema II is ready to implement School-Based Management by forming a school committee, (2) The Principal has a very important role in implementing School Based Management, (3) Attitude of Stakeholders in the implementation of School-Based Management at SD Inpres Kema II is positive, (4) Obstacles in the form of differences of opinion, not involving themselves in every school work program are still inherent in a small portion of the school community, (5) Two-way communication between leaders and subordinates is needed in Overcoming obstacles that occur can take the form of motivation and training.